PENGARUH SELF COMPASSION TERHADAP RESILIENSI REMAJA PADA SISWA DI SMA NEGERI 3 BINJAI - Hasanah, Nurul; -, Mardiati; Ardianti, Windi; Sitepu, Fatmawati (unprimdn.ac.id, 2024)
One of the important abilities in adolescent development is resilience because the social, biological, and psychological changes experienced by adolescents require them to be adaptive in dealing with problems. In this condition, they need self-compassion to accept all the external challenges related to problems with family, school, and an uncertain future. This study aims to determine the effect of Self Compassion on Adolescent Resilience. This research was conducted at SMA Negeri 3 Binjai. This research method uses non-test techniques in the form of a questionnaire (questionnaire). The sample of this study amounted to 86 XII students. The sampling technique was done randomly. This study used simple regression analysis to see how much influence SELF COMPASSION HAS ON YOUTH RESILIENCE IN STUDENTS AT SMA NEGERI 3 BINJAI. The results showed that self-compassion influenced adolescent resilience in SMA Negeri 3 Binjai students. This is indicated by tcount> table (33.205> 1.667) and p = 0.000. Furthermore, based on the results of the variable influence test, the R Square value is 0.929 (92.9%). This shows that self-compassion has an influence on resilience by 92.9%. Meanwhile, 7.1% is influenced by other factors.